Upaya Awal Meningkatkan Nilai Ekonomi Kolesom Jawa Melalui Teknik Budidaya Stek Batang - Diah Ayu Retnani Wulandari; Sri Hartatik; Kacung Hariyono (Ilin Institute, 2021)
Arjasa village has productive land for agriculture. In the rainy season, the plants grow thick, which can disturb the environment. The observation result was found kolesom plant. Kolesom has economic value because many benefits, but worthless in the Arjasa village. Kolesom is worthless because residents do not know the benefits. Efforts are made through several activities. This activity requires two years because the kolesom harvest time. The first year there are socialization for introduction, training on kolesom cultivation, and the second year is continued with the commercialization of the kolesom. In this article, we will discuss the activities of the first year in the form of socialization and training on kolesom cultivation using stem-cutting techniques. The socialization activities results are in the form of increased knowledge regarding the benefits and cultivation of the kolesom. Some evidence is that the community, started planting in the yard and the posyandu in Arjasa village began planting around the posyandu. In this activity, evidence was obtained that the determining factor for the success of the cultivation of stem cutting techniques at the kolesom was the selection of stems which had to be reddish-brown in color, placing the stems in soil media could not be reversed because the roots did not grow.